Hairhealth: A mobile application for alopecia and psoriasis identification using image processing and data mining - Pasadilla, Catherine L.; Rubio, Joan H.; Signey, Jasmine Risha L. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2